Extremity soft-tissue sarcomas – reconstructive strategy of the post surgical resection - K. Dobke, Marek; L. Clark, Norman (Contemporary Oncology/Współczesna Onkologia, 1999)
Based on the authors’ experience with twenty patients with extremity sarcoma who underwent reconstructive surgery subsequent to tumor resection and the review of current literature, the strategy of reparative approach is discussed. Such topics as the principles of planning, technical alternatives, results and complications of extremity reconstruction are reviewed. The utility of single-stage primary sarcoma resection, soft-tissue reconstruction, and radiotherapy for extremity preservation is presented. In patients who are unable to undergo primary wound closure after a complete resection, pedicled and free tissue flaps provide adequate wound coverage even in the setting of early postoperative brachyterapy.